Gender disparities in the adoption of improved management practices for soybean cultivation in North East Nigeria - Amadu Yaya Kamara; Lucy Sahbong Kamsang; Amina Mustapha; Alpha Yaya Kamara; Adetomiwa Kolapo; Nkeki Kamai (Journal of Agriculture and Food Research)
This study examined gender disparities in the adoption and intensity of improved soybean management practices among 800 farming households in Borno State, Nigeria, with equal representation of male-led and female-led households. The findings reveal that while both male and female farmers adopt improved soybean varieties, fertilizer, and herbicides, the intensity of adoption varies due to differences in socioeconomic constraints. Male farmers demonstrated slightly higher adoption rates across all practices, particularly for herbicide use. However, financial and market-related barriers, such as high input costs and distance to seed markets, disproportionately hindered female farmers' ability to fully integrate improved practices into their farming activities. The analysis indicates that the adoption of improved soybean varieties by male farmers was mainly influenced by income and pest/disease constraints, whereas female farmers were more affected by age, extension visits, and community tenure. Herbicide use among male farmers was driven by farm size and input costs, while for female farmers, it was influenced by education, input costs, and proximity to seed markets. Fertilizer adoption among male farmers was linked to income and farming experience, whereas female farmers' fertilizer use was shaped by farm size and financial constraints. Ordered probit regression results suggest that age negatively affects adoption intensity for both genders, but income and community tenure play a stronger role for men, while market access and cost barriers are more significant for women. Improving access to extension services can significantly enhance adoption rates, especially for female farmers who face higher input costs and limited access to seed markets. Targeted subsidies and credit programs tailored to smallholder farmers will help alleviate financial barriers, enabling both men and women to invest in essential inputs and expand production. Strengthening rural infrastructure, including better road networks and input market accessibility, will further reduce logistical challenges and support increased soybean cultivation.